Local public transport planning in Poland - geographical input - Chaberko Tomasz; Kretowicz Paweł (Bulletin of Geography. Socio-Economic Series, 2014)
This paper concentrates on geographical contribution to public transport planning in Poland with a special regard to transport services of general interest. The authors draw on the newly enacted Polish legislative acts concerning public transportation: the Act of 16 December 2010 on public transport and the Regulation of 25 May 2011 on the detailed scope of sustainable development plan of public transport. According to these legal acts, authorities of the largest local and regional governments in Poland are obliged to prepare public transport plans by March 2014. In order to provide useful guidelines that would ameliorate the preparation of public transportation plans by these authorities, the authors demonstrate some effective examples of geographical analyses utilising sample cases of a medium-sized city (Gdynia) and a medium-sized poviat (Krosno poviat). The authors explain how to delineate the network of public transport of general interest in these administrative units along with route categorisation. Additionally, some principles of the city area division into public transportation sectors - a spatial unit facilitating public transport planning - are presented on the example of Gdynia.